IDDF2022-ABS-0275 Clostridium btyricum and metabolite butyrate relieve DSS-induced colitis in mice by regulating IGA-coated microbiota. (2nd September 2022) - Xu, Jing; Xu, Haoming; Guo, Xue; Huang, Wenqi; Peng, Yao; Wang, Jiaqi; Zhao, Hailan; Zhang, Yong; Zhou, Youlian; Nie, Yuqiang
Abstract : Background: Gut microbiota and its metabolites are important factors affecting the treatment and progression of ulcerative colitis, but the mechanism was still unclear. This study aims to study the efficacy of Clostridium butyricum MIYAIRI 588 (CBM) on colitis mice and explore the effect on IgA-coated microbiota of CBM and metabolite butyrate. Methods: Twenty-four Balb/c mice with specific pathogen-free were randomly divided into four groups of six mice each. The Control group were fed normal drinking water, and the other three groups were drinking water which contained 3% DSS for seven days. In this study, CBM (10 6 CFU/mL) and its main metabolite butyrate (0.2mg/kg) were used to intervene in the colitis mouse by oral gavage. The changes in weight loss, colon length and histopathology of colitis mice were observed and recorded. RNA-sequencing was used to detect the transcriptional changes in the colon in mice, and the percentage of IgA-coated microbiota in feces was detected by flow cytometry. Results: From the fourth day after the intervention of CBM and butyrate, the weight loss and colon shorten of colitis mice had been alleviated (IDDF2022-ABS-0275 Figure 1A. Weight loss of mice after CBM and butyrate treatment) (IDDF2022-ABS-0275 Figure 1B. Colon length of mice). Besides, CBM and metabolite butyrate can relieve the colonic pathology, which is reflected in reducing the damage of the mucosa structure and the infiltration of inflammatory cells (IDDF2022-ABS-0275 Figure 1C. Histopathological analysis of colon sections which stained by hematoxylin-eosin staining). RNA-sequencing showed that by KEGG enrichment analysis of differentially expressed genes, numerous signaling pathways concerning immunity and metabolism could be observed, including the pathway of the intestinal immune network for IgA production (IDDF2022-ABS-0275 Figure 1D. KEGG enrichment analysis of butyrate treatment on colitis mice). Furthermore, results showed that the proportion of IgA-coated microbiota in cecal contents of mice with colitis increased significantly. However, both CBM and metabolite butyrate could significantly reduce the proportion of IgA-coated microbiota (IDDF2022-ABS-0275 Figure 1E. The proportion of IgA-coated microbiota after CBM and butyrate treatment) (IDDF2022-ABS-0275 Figure 1F. The statistical analysis of the percentage of IgA-coated microbiota). Conclusions: The present study confirmed that CBM and metabolite butyrate could effectively alleviate DSS-induced colitis, might through regulating mucosal immune homeostasis by affecting IgA-coated microbiota. In summary, our study explored the interaction between gut microbiota and host immunity, and it provides theoretical support for the better use of probiotics.